An observational pilot study to collect safety and efficacy data on wound care using whole blood clot technology on hard-to-heal wounds. Issue 2 (19th May 2021) - Naude, Liezl; Idensohn, Patricia; Bruwer, Febe; Balenda, Georges; Gurevich, Maxim; Mulder, Magda; Matityahu, Moreno; Izakson, Yael; Fridman, Ruhama; Rech, Dino
No abstract available